OFSP Takes Off as Part of the New Accelerated Value Chain Development Program in Kenya - International Potato Center (2016)
During the first 11 months of this program, we have reached over 9,000 households with OFSP planting material. The total vine multiplication area under Decentralized Vine Multipliers has increased to 6.2 hectares. We have trained 772 health workers and they have started reaching out to child care givers and pregnant mothers to improve infant and young child feeding practices.